Clinical differences in Clostridium difficile infection based on age: A multicenter study. (January 2014) - Kim, Hyung Hun; Kim, You Sun; Han, Dong Soo; Kim, Young-Ho; Kim, Won Ho; Kim, Joo Sung; Kim, Hyunsoo; Kim, Hyun-Soo; Park, Young-Sook; Song, Hyun Joo; Shin, Sung Jae; Yang, Suk-Kyun; et al.
Abstract: Advancing age is a well-known risk factor for Clostridium difficile infection (CDI). However, age-specific clinical differences in CDI are uncertain. A retrospective comparative analysis was performed based on age in 1367 patients with CDI in Korea. Most clinical features were similar in the two age groups studied, however malignancy was more common in the older group (age ≥ 65 y) ( p < 0.001), while chemotherapy and transplantation were more common in the younger group (age < 65 y) ( p < 0.001). Endoscopic examinations were more commonly performed in the older group ( p = 0.010), which had a high positive predictive value (88.3%). More patients recovered from CDI without specific antibiotic treatment in the younger group than in the older group ( p < 0.001). Although advancing age is an important risk factor for CDI, the clinical features of younger patients are similar to those of the older patient population.